2018
DOI: 10.1016/j.pjnns.2018.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive decompression in patients with degenerative spondylolisthesis associated with lumbar spinal stenosis. Report of a surgical series and review of the literature

Abstract: We reported the results of minimally invasive spinal decompression (MISD) in patients with degenerative spondylolisthesis (DS) associated with lumbar spinal stenosis (LSS) and performed a literature review in order to evaluate the clinical and radiological outcomes, the complications and reoperation rate of MISD procedures in these patients. Data of 28 patients submitted to MISD for DS associated to LSS were reviewed. We evaluated the Visual Analogue Scale (VAS) both for low back pain (LBP) and legs pain, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Rahman [53]. A systematic review describing MISD for degenerative spondylolisthesis found an overall complication rate of 1.6% and an overall reoperation rate of 4.5% [55]. Another systematic review exploring minimally invasive discectomy versus microdiscectomy and open discectomy in lumbar disc herniation cases found lower rates of surgical site infections and urinary tract infections, yet higher rates of rehospitalization for recurrent disc herniation [56].…”
Section: Discussionmentioning
confidence: 99%
“…Rahman [53]. A systematic review describing MISD for degenerative spondylolisthesis found an overall complication rate of 1.6% and an overall reoperation rate of 4.5% [55]. Another systematic review exploring minimally invasive discectomy versus microdiscectomy and open discectomy in lumbar disc herniation cases found lower rates of surgical site infections and urinary tract infections, yet higher rates of rehospitalization for recurrent disc herniation [56].…”
Section: Discussionmentioning
confidence: 99%
“…When conservative treatment thoroughly fails, surgical treatment is considered. 2 Traditionally, decompression with instrumented fusion procedures has been performed for patients with neurogenic claudication and nerve root compression. Ghogawala et al 3 concluded that among patients with DLS, the addition of fusion was associated with significant improvements in quality of life compared with decompression alone.…”
Section: Introductionmentioning
confidence: 99%
“…We prospectively collected the clinical and radiological data of 24 consecutive patients (16 F, 8 M) submitted to MID 18 for the treatment of lumbar spinal stenosis (LSS), from January 2019 to March…”
Section: Methodsmentioning
confidence: 99%
“…We prospectively collected the clinical and radiologic data of 24 consecutive patients (16 females and 8 males) submitted to MID 18 for the treatment of LSS, from January to March 2019. One of the patients declined after reading the informed consent, two patients were excluded because they were affected by rheumatic disorder (polymyalgia rheumatic), and one was affected by lumbar spondylolisthesis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation